Protein metabolism in cirrhotic rats: effect of dietary restriction - Holecek, M; Skopec, F; Sprongl, L (Annals of nutrition & metabolism, 1995)
This paper evaluates the role of decreased food intake in protein metabolism in cirrhotic animals by comparing the changes with those observed in pair-fed controls. Rats were injected with [14C]leucine and then divided into 3 groups. Liver cirrhosis was induced in 1 group of rats by repeated intragastric administration of CCl4 in oil over a period of 8 weeks. Control animals were gavaged with oil and either pair-fed or given access to food ad libitum. Three days after the last intragastric dose, rats were injected with [3H]leucine and sacrificed 20 min later. The daily food intake of CCl4 rats declined to 60% of that of the ad libitum controls. Both the pair-fed control group and the cirrhotic group showed decreased body weight gain, and a decline in muscle and intestinal protein degradation. The pair-fed and the cirrhotic groups differed from one another in many metabolic abnormalities. In the cirrhotic group we observed higher levels of serine, asparagine, proline, methionine, tyrosine, phenylalanine, ornithine and histidine, and lower levels of valine, isoleucine and arginine. In these animals higher relative (per kilogram body weight) weights and protein content of the spleen, kidneys and heart were observed. Additionally higher liver weight despite lower protein concentration, as well as lower liver protein degradation and lower skeletal muscle protein synthesis were found.
Keywords: aminokyseliny; velikost orgánu; proteiny; Male; Rats, Wistar; slezina; leucin; Organ Size; experimentální cirhóza jater; potravinová deprivace; Intestine, Small; Myocardium; Kidney; Leucine; chlorid uhličitý; mužské pohlaví; potkani Wistar; Body Weight; Food Deprivation; Spleen; krysa rodu Rattus; Liver Cirrhosis, Experimental; Animals; játra; ledviny; zvířata; Rats; tenké střevo; Liver; Carbon Tetrachloride; Proteins; tělesná hmotnost; myokard; Amino Acids